Blood donors’ knowledge and attitude towards blood donation at North Gondar district blood bank, Northwest Ethiopia: a cross-sectional study - Bamlaku Enawgaw (BMC Research Notes, 2019)
Abstract Objective Blood transfusion saves millions of lives. But, the need and the actual number of donations are not balanced in Ethiopia. The actual reason is not clearly assessed; however, level of knowledge and attitude may be the main contributing factors. Thus, the current study aimed to assess blood donors’ knowledge and attitude towards blood donation at North Gondar district blood bank. Results Of 401 blood donors, 142 (35.4%) and 379 (94.5%) were had adequate knowledge and positive attitude towards blood donation, respectively. About 343 (85.5%) of study participants had no previous experience of blood donation. Perceptions of fear of pain, medically unfitness to donate and lack of information on when, where and how to donate blood were mentioned as a reason for not donating blood. Educational status and residence were significantly associated with knowledge of blood donors. On the other hand, participants with secondary and higher education were more likely to have good attitude towards blood donation. Thus, blood banks should design strategies for health education about blood donation and transfusion.